Sudanese farmers take to donkey power - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
In Darfur Province, west Sudan, donkeys are gradually becoming the main draught animal. This has been made possible because a chisel plough based on the ancient ard plough, has been developed especially for use with donteys. Although camels have...